(untitled) (Research, Society and Development, 2019)
The objective of the present work was to analyze the possibility of the incidence of Law 11.340/06 in the crime of mistreatment, foreseen in art. 136 of the Penal Code, when it is a female victim, as well as the possibility of changing the jurisdiction for the trial, considering that the mistreatment is a crime of lesser offensive potential, with maximum penalty less than two years, being of original jurisdiction of the Special Criminal Court, admitting all the decriminalizer institutes brought by Law 9.099/95. Moreover, in this work, the deductive method was used, with the research in doctrines, legislation and, mainly, in jurisprudence. Finally, it was concluded that the understanding that should be taken into consideration is that the trial of the crime of ill-treatment perpetrated against a female taxpayer should be carried out by Special Criminal Courts, since, for the characterization of ill-treatment, it is necessary not only the relationship of subordination between agent and victim, but also a special purpose to act on the part of the offender, the content of art. 136 of the Penal Code, in respect of the principle of legality and the principle of subjective responsibility of Criminal Law. This is because the perpetrator can only be punished for what was in his orbit of knowledge and/or intention, as well as for what is expressly provided for by law.